(untitled) (Web of Teachers: Inderscience Research, 2023)
In this article, we will discuss and discover about what is blockchain, and their three important concepts: blocks, nodes and miners. And aslo you are given information about six main facts of blockchain. The blockchain is an ingenious and remarkable invention. This technology created the backbone of a new type of internet. It was originally designed for the digital currency, bitcoin, in which you can send digital money to anyone, even a stranger.